2021
DOI: 10.3341/kjo.2021.0076
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Scheimpflug Camera and the Swept-source Optical Coherence Tomography Measurements in Keratometry and Higher-order Aberrations

Abstract: To evaluate the compatibility of corneal curvature and astigmatism, and higher-order aberrations (HOAs) measured by the Scheimpflug camera Pentacam HR and the swept-source optical coherence tomography ANTERION.Method: This prospective study included normal subjects with no ophthalmic history. Steep keratometry (K), flat K, astigmatism and its axis of the anterior and posterior surfaces, total corneal power, and HOAs using the two instruments were compared. To compare the mean values of the measurements, a pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Similar results were obtained in the present study with LoA of -0.03 to 0.86 D between Anterion and CASIA2. Gim et al [12] showed good agreement between Anterion and Pentacam for at and steep TCP with the maximum absolute LoA ≤ 0.61 D, which were close to our results with the maximum absolute LoA ≤ 0.48 D.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar results were obtained in the present study with LoA of -0.03 to 0.86 D between Anterion and CASIA2. Gim et al [12] showed good agreement between Anterion and Pentacam for at and steep TCP with the maximum absolute LoA ≤ 0.61 D, which were close to our results with the maximum absolute LoA ≤ 0.48 D.…”
Section: Discussionsupporting
confidence: 92%
“…-0.3643 to 0.5069 D for at sim-K; LoA: -0.3705 to 0.5638 D for steep sim-K) 13 . Flat and steep sim-K showed good agreement between Anterion and Pentacam in the study by Gim et al [12] with the maximum absolute LoA ≤ 0.50 D. Similar results were obtained in the current study, good agreement was acquired for both at and steep sim-K between Anterion and Pentacam with LoA of -0.18 to 0.48 D and − 0.36 to 0.40 D, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…No studies are currently evaluating the agreement between MS-39 measurements of corneal aberrations and those by other devices. Recent studies have reported agreement between the Anterion and Pentacam HR devices for corneal aberrations in healthy subjects [36,37]. Pe ´rez-Bartolome ´et al [36] indicated that vertical coma and RMS HOA values had good agreement, as the 95% LoAs ranged from -0.37 to 0.308 lm and from -0.27 to 0.305 lm, respectively.…”
Section: Discussionmentioning
confidence: 97%